2017
DOI: 10.1111/1462-2920.13611
|View full text |Cite
|
Sign up to set email alerts
|

Plant–phytopathogen interactions: bacterial responses to environmental and plant stimuli

Abstract: Summary Plant pathogenic bacteria attack numerous agricultural crops, causing devastating effects on plant productivity and yield. They survive in diverse environments, both in plants, as pathogens, and also outside their hosts as saprophytes. Hence, they are confronted with numerous changing environmental parameters. During infection, plant pathogens have to deal with stressful conditions, such as acidic, oxidative and osmotic stresses; anaerobiosis; plant defenses; and contact with antimicrobial compounds. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 210 publications
(298 reference statements)
1
50
0
1
Order By: Relevance
“…It is important to note that because of the difficulty associated with identification and quantification of antibiotics and bacteriocins produced by bacteria in planta , most studies, including the current study, make inferences based on in vitro detection of these compounds and extrapolations/inferences are made to in planta conditions based on the assay conditions which mimic plant apoplast (minimal media and anaerobic conditions) (65). Against this background it is possible that Pcb 1692 does not produce carbapenem in planta but is able to produce bacteriocins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that because of the difficulty associated with identification and quantification of antibiotics and bacteriocins produced by bacteria in planta , most studies, including the current study, make inferences based on in vitro detection of these compounds and extrapolations/inferences are made to in planta conditions based on the assay conditions which mimic plant apoplast (minimal media and anaerobic conditions) (65). Against this background it is possible that Pcb 1692 does not produce carbapenem in planta but is able to produce bacteriocins.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, recent studies have shown that bacterial SOS can be triggered directly or indirectly by different factors such as nutrient starvation, iron deficiency, chromate stress, acidic and alkaline stress, oxidative stress and β-lactam antibiotics (10, 66-69). All the above scenarios can be encountered by Pcb in planta , for example, one of the first stresses encountered by Pcb , SREs and other endophytes in potato tubers is acidic pH, which SREs must neutralize to be able to produce PCWDEs (65, 70, 71). Similarly, intake of excess iron can lead to oxidative burst in bacteria through Fenton reaction (72).…”
Section: Discussionmentioning
confidence: 99%
“…It like many phytopathogenic bacteria produce multiple extracellular plant cell wall degrading enzymes. Some of these enzymes have been implicated as virulence factors contributing to the pathogen ability to invade and colonize host tissues causing the wilt disease (Liu et al,2005;Leonard et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…by pectinolytic pathogens are soft rot and blackleg, respectively. These pathogens produce a large set of extracellular enzymes that break down the plant cell wall, resulting in plant tissue decay and maceration [3]. These pathogens cause important losses to the production of potato tubers for food market, and all along the certification steps of tuber seeds.…”
mentioning
confidence: 99%